Massive parallel sequencing of head and neck conventional squamous cell carcinomas: A comprehensive review - Nadal, Alfons; Cardesa, Antonio; Agaimy, Abbas; Almangush, Alhadi; Franchi, Alessandro; Hellquist, Henrik; Leivo, Ilmo; Zidar, Nina; Ferlito, Alfio (Springer Science and Business Media LLC, 2025)
Head and neck squamous cell carcinoma (HNSCC) is the sixth most common cancer worldwide and is a cause of significant mortality and morbidity. The epidemiology of this cancer varies worldwide due to either genetic differences in populations or differences in carcinogen exposure. The application of massive parallel sequencing-based techniques in HNSCC should provide a helpful understanding of the genetic alterations that eventually lead to HNSCC development and progression, and ideally, could be used for personalized therapy. In this review, the reader will find an overview of the mutational profile of conventional HNSCC according to published results on massive parallel sequencing data that confirm the pivotal role of TP53 and the frequent involvement of CDKN2A and PIK3CA. The reader will also find a more detailed description of the genes, such as NOTCH1 and FBXW7, that were not identified in HNSCCs before the development of these techniques, the differences that can be site-specific, such as the different mutational signatures that indicate specific carcinogens for various subsites of the head and neck, and finally, the actionability of these findings that should allow more personalized therapy for patients.